PROSPECTS FOR THE DEVELOPMENT OF MICE TOURISM IN OUR COUNTRY - Ergashev Doniyor Ixtiyorovich (Лучшие интеллектуальные исследования, 2024)
Abstract: Mice tourism is a well-known part of the tourism industry, it is one of the important jewels of the tourism industry and its benefits to the country's economy are detailed in the article. About what MICE tourism is, how the MICE tourism industry has developed around the world, and why this type of tourism is so important. MICE stands for Meetings, Incentives, Conferences and Exhibitions and it represents a profitable part of the tourism mix worldwide. MICE can also be called business tourism or business events.